PEDAGOGICAL FOUNDATIONS OF USING HISTORICAL AND CULTURAL HERITAGE IN THE TRAINING OF ENGINEERING PEDAGOGUES (Multidisciplinary Journal of Science and Technology, 2025)
This article examines the pedagogical foundations of using historical and cultural heritage in the process of training engineering pedagogues. The study explores the role of cultural heritage in education, its impact on strengthening national identity, fostering moral and ethical values, and developing professional competencies. By analyzing Uzbekistan’s experience in comparison with international practices, the article highlights practical mechanisms for integrating architectural monuments, the scientific legacy of great scholars, and ancient engineering achievements into the learning process. The findings demonstrate that the effective use of historical and cultural heritage serves as a bridge between theory and practice in higher education and contributes to the formation of engineering pedagogues as specialists who combine technical knowledge with national and cultural values.